Towards human organ generation using interspecies blastocyst complementation: Challenges and perspectives for therapy - Sarmah, Hemanta; Sawada, Anri; Hwang, Youngmin; Miura, Akihiro; Shimamura, Yuko; Tanaka, Junichi; Yamada, Kazuhiko; Mori, Munemasa (Frontiers in Cell and Developmental Biology, 2023)
Millions of people suffer from end-stage refractory diseases. The ideal treatment option for terminally ill patients is organ transplantation. However, donor organs are in absolute shortage, and sadly, most patients die while waiting for a donor organ. To date, no technology has achieved long-term sustainable patient-derived organ generation. In this regard, emerging technologies of chimeric human organ production via blastocyst complementation (BC) holds great promise. To take human organ generation via BC and transplantation to the next step, we reviewed current emerging organ generation technologies and the associated efficiency of chimera formation in human cells from the standpoint of developmental biology.